An Ultrastable Anode for Long‐Life Room‐Temperature Sodium‐Ion Batteries1. (24th June 2014) - Yu, Haijun; Ren, Yang; Xiao, Dongdong; Guo, Shaohua; Zhu, Yanbei; Qian, Yumin; Gu, Lin; Zhou, Haoshen
Abstract Sodium‐ion batteries are important alternative energy storage devices that have recently come again into focus for the development of large‐scale energy storage devices because sodium is an abundant and low‐cost material. However, the development of electrode materials with long‐term stability has remained a great challenge. A novel negative‐electrode material, a P2‐type layered oxide with the chemical composition Na2/3Co1/3Ti2/3O2, exhibits outstanding cycle stability (ca. 84.84 % capacity retention for 3000 cycles, very small decrease in the volume (0.046 %) after 500 cycles), good rate capability (ca. 41 % capacity retention at a discharge/charge rate of 10 C), and a usable reversible capacity of about 90 mAh g−1 with a safe average storage voltage of approximately 0.7 V in the sodium half‐cell. This P2‐type layered oxide is a promising anode material for sodium‐ion batteries with a long cycle life and should greatly promote the development of room‐temperature sodium‐ion batteries.